2021
DOI: 10.1093/tropej/fmab068
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms Profile and Antimicrobial Resistance Pattern in Outborn Neonates in Northern India: A Hospital-Based Observational Study

Abstract: Background Neonates born somewhere else (outborn) and treated in a referral centre have different microbiological profile. We report the microorganism’s profile and antimicrobial resistance (AMR) in blood culture proven sepsis in outborn neonates. Methods Culture positive neonatal sepsis from a neonatal unit of a referral institute catering to outborn neonates was studied over an 18 months duration. Data from the hospital inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In India, clinicians over the past 10 years are turning more frequently to colistin as part of routine practice (19). Worryingly, our study showed higher rates of colistin resistance (14% overall, 30% in K. pneumoniae isolates) than previously reported in the literature on neonates in India (0-10%) (3,(20)(21)(22)(23)(24)(25). Polymyxins are classified as a "reserve" antibiotic class by the WHO (26).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In India, clinicians over the past 10 years are turning more frequently to colistin as part of routine practice (19). Worryingly, our study showed higher rates of colistin resistance (14% overall, 30% in K. pneumoniae isolates) than previously reported in the literature on neonates in India (0-10%) (3,(20)(21)(22)(23)(24)(25). Polymyxins are classified as a "reserve" antibiotic class by the WHO (26).…”
Section: Discussionmentioning
confidence: 60%
“…Of infections with a central line present at time of positive culture, the median for total duration of central line use was 6 days (IQR 4-12). The median time to culture positivity (from incubation to growth) was 22 h (IQR [19][20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…[2] and Bipin Gupta et al [9]. These gram negative bacteria were resistant to third-generation cephalosporins [10].…”
Section: Discussionmentioning
confidence: 99%